2015
DOI: 10.1590/s0104-64972015002325
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive aspects of Hyalella carstica (Amphipoda: Hyalellidae) in a natural environment in southeastern Brazil

Abstract: Th e reproductive aspects of populations are important determinants of their ability to maintain themselves throughout time. In the case of amphipods from the genus Hyalella Smith, 1874, the reproductive period is easily determined by the presence of ovigerous females and pre-copula pairs in the population. Th is study evaluated the fecundity, pairing patterns and reproduction period of Hyalella carstica Bastos-Pereira and Bueno, 2012 in a karst environment in the West of Minas Gerais, Brazil. Monthly, from Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
2
4
0
2
Order By: Relevance
“…The number of pairs in precopulatory mate-guarding behavior in the population of H. palmeirensis was slightly low, when compared to unpaired adults. The same was observed in Hyalella castroi and H. pleoacuta (Castiglioni & Bond-Buckup 2008b), H. carstica (Torres et al 2015) and H. bonariensis (Castiglioni et al 2018). The low occurrence of pairs in this population can be related to the fact that the individuals stay in precopulatory mate-guarding for a short time, approximately 3-4 days (personal observation), since this behavior can make individuals more vulnerable to predation (Strong 1972;Wellborn 1995;Castiglioni & Bond-Buckup 2008b).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The number of pairs in precopulatory mate-guarding behavior in the population of H. palmeirensis was slightly low, when compared to unpaired adults. The same was observed in Hyalella castroi and H. pleoacuta (Castiglioni & Bond-Buckup 2008b), H. carstica (Torres et al 2015) and H. bonariensis (Castiglioni et al 2018). The low occurrence of pairs in this population can be related to the fact that the individuals stay in precopulatory mate-guarding for a short time, approximately 3-4 days (personal observation), since this behavior can make individuals more vulnerable to predation (Strong 1972;Wellborn 1995;Castiglioni & Bond-Buckup 2008b).…”
Section: Discussionsupporting
confidence: 69%
“…The mean fecundity of H. palmeirensis is relatively lower than other species of Hyalella that occur in the state of Rio Grande do Sul, such as H. pleoacuta and H. castroi (Castiglioni & Bond-Buclup 2009), and H. gauchensis and H. georginae (Ozga & Castiglioni 2017) and similar to H. bonariensis (Castiglioni et al 2018). Castiglioni et al (2018) observed for H. bonariensis greater fecundity compared to other Brazilian tropical species, such as H. carstica (Torres et al 2015) and H. longistila (Bastos-Pereira & Bueno 2016) and one North American species, H. azteca (Othman & Pascoe 2001;Wellborn et al 2005). Probably, this difference in fecundity between species of the genus Hyalella may be associated with differences in habitats and microclimate in which species live, a fact already verified by Poweel (1992) and Appadoo & Myers (2004) for other amphipod species.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Ovigerous females of H. pampeana were collected in most of the months, indicating that reproduction is continuous in this species throughout the year, in agreement with data reported by lopretto (1983) in ponds of the province of Buenos Aires, Argentina. Continuous reproduction has been reported in other Hyalella species that inhabit natural populations in tropical and subtropical temperature regimes (edwards and Cowell 1992, Castiglioni and Bond-Buckup 2009, Bastos-Pereira and Bueno 2016, Ozga and Castiglioni 2017, Torres et al 2015, Castiglioni et al 2016). According to Sainte-Marie (1991), gammaridean populations exhibit reproductive patterns that can be associated with latitude.…”
Section: Population Structure and Recruitmentmentioning
confidence: 89%
“…A positive correlation between the female size and the number of eggs/juveniles was observed in H. bonariensis. Several authors observed an association between females' size/weight and the number of embryos in other Hyalella species (Strong 1972;Othman & Pascoe 2001;Alcocer et al 2002;Castiglioni & Bond-Buckup 2007Torres et al 2015;Bastos-Pereira & Bueno 2016). According to Hines (1988), this association may be linked to the fact that the egg mass is restricted by the space available for energetic accumulation and gonadal development.…”
Section: Discussionmentioning
confidence: 99%